A New Iterative Method for Suzuki Mappings in Banach Spaces. (28th February 2021) - Ahmad, Junaid; Ullah, Kifayat; Arshad, Muhammad; Ma, Zhenhua
Abstract : In this paper, an efficient new iterative method for approximating the fixed point of Suzuki mappings is proposed. Some important weak and strong convergence results of the proposed iterative method are established in the setting of Banach space. An example illustrates the theoretical outcome.